2008
DOI: 10.1016/j.brainres.2007.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Potent induction of total cellular GSH and NQO1 as well as mitochondrial GSH by 3H-1,2-dithiole-3-thione in SH-SY5Y neuroblastoma cells and primary human neurons: Protection against neurocytotoxicity elicited by dopamine, 6-hydroxydopamine, 4-hydroxy-2-nonenal, or hydrogen peroxide

Abstract: Evidence suggests oxidative and electrophilic stress as a major factor contributing to the neuronal cell death in neurodegenerative disorders, especially Parkinson's disease. Consistent with this concept, administration of exogenous antioxidants has been shown to be protective against oxidative/ electrophilic neurodegeneration. However, whether induction of endogenous antioxidants and phase 2 enzymes by the unique chemoprotectant, 3H-1,2-dithiole-3-thione (D3T) in neuronal cells also affords protection against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…107 Oxidative stress in spinal cord injury Z Jia et al that D3T increases multiple cellular antioxidants including glutathione and NQO1, two crucial cellular defenses against oxidative and electrophilic stress in human neuroblastoma cells (SH-SY5Y), human primary neurons and astrocytes, suggesting that D3T-mediated antioxidant induction is not cell-type specific. [60][61][62] In addition, D3T treatment of the neuronal cells also results in a marked elevation of glutathione content in the mitochondrial compartment, 62 a critical intracellular target for oxidative and electrophilic stress. 63 It is important to note that the D3T upregulated endogenous defenses are accompanied by increased cellular resistance to neurocytotoxicity elicited by ROS and several well-known neurotoxins including acrolein, suggesting a potential therapeutic value in SCI.…”
Section: Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Oxidative stress in spinal cord injury Z Jia et al that D3T increases multiple cellular antioxidants including glutathione and NQO1, two crucial cellular defenses against oxidative and electrophilic stress in human neuroblastoma cells (SH-SY5Y), human primary neurons and astrocytes, suggesting that D3T-mediated antioxidant induction is not cell-type specific. [60][61][62] In addition, D3T treatment of the neuronal cells also results in a marked elevation of glutathione content in the mitochondrial compartment, 62 a critical intracellular target for oxidative and electrophilic stress. 63 It is important to note that the D3T upregulated endogenous defenses are accompanied by increased cellular resistance to neurocytotoxicity elicited by ROS and several well-known neurotoxins including acrolein, suggesting a potential therapeutic value in SCI.…”
Section: Nucleusmentioning
confidence: 99%
“…63 It is important to note that the D3T upregulated endogenous defenses are accompanied by increased cellular resistance to neurocytotoxicity elicited by ROS and several well-known neurotoxins including acrolein, suggesting a potential therapeutic value in SCI. [60][61][62] Other compounds: several epidemiological studies have demonstrated that increased consumption of antioxidant-rich fruits and vegetables is associated with reduced risk of ischemic stroke, dementia and SCI. 64,65 In this context, identification and study of the biologically active compounds may be of importance for developing strategies to inhibit, retard or reverse the pathophysiological processes underlying SCI.…”
Section: Nucleusmentioning
confidence: 99%
“…It was found that the induction of free radical production, that can further lead an oxidative stress, is nonspecific reaction to a wide range a stress factors [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of NQO1 by sulforaphane, dimethyl fumarate, 3H-1,2-dithiole-3-thione, tert-butylhydroquinone (tBHQ), and butylated hydroxyanisole protected against neurocytotoxicity associated with DA quinone in vitro (H.J. Choi et al, 2003;Duffy et al, 1998;Han et al, 2007;Hara et al, 2003;Jia et al, 2009;Jia et al, 2008;Miyazaki et al, 2006;Siebert et al, 2009);; and against MPTP-elicited toxicity in vivo (Jazwa et al, 2011). In addition, NQO1 is known to maintain both -tocopherol and coenzyme Q10 in their reduced, antioxidant state (Siegel et al, 1997).…”
Section: Nqo1 and Its Inducers As Protective Agentsmentioning
confidence: 99%
“…Indeed, the toxic accumulation of the DA quinone (as well as L-DOPA quinone) can be prevented by the action of NQO1. NQO1 protected against damaging effects of cyclized quinones and oxidative stress induced during their redox cycling (Zafar, Inayat-Hussain, et al, 2006), and against DA (Zafar, Siegel, et al, 2006) and 6-hydroxyDA (Jia et al, 2008). Induction of NQO1 by sulforaphane, dimethyl fumarate, 3H-1,2-dithiole-3-thione, tert-butylhydroquinone (tBHQ), and butylated hydroxyanisole protected against neurocytotoxicity associated with DA quinone in vitro (H.J.…”
Section: Nqo1 and Its Inducers As Protective Agentsmentioning
confidence: 99%